Variation of undrained shear strength of clay with depth / Intan Rohani Endut - Endut, Intan Rohani (1996)
The main objective of this project is to find the relationship of the ratio of undrained shear strength with depth and Plasticity index of clay. Besides that the study also obtained the phyiscal and engineering properties of the clay. Based on existing data and results from this project, shown that the for different location, the physical and engineering properties of the clay are different. The results of the study was plotted based on the correlation provided by Skempton. It was found that the data obtained were scattered around the correlation proposed by Skempton. The results for Shah Alam clay fall above the line and Batu Belah fall below. However, no conclusive correlation could be deduced as it was feit the data so far are insufficiënt.